2019
DOI: 10.1038/s41598-019-54201-2
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-clinical Animal Model of Secondary Head and Neck Lymphedema

Abstract: Head and neck lymphedema (HNL) is a disfiguring disease affecting over 90% of patients treated for head and neck cancer. Animal models of lymphedema are used to test pharmacologic and microsurgical therapies; however, no animal model for HNL is described in the literature to date. In this study we describe the first reproducible rat model for HNL. Animals were subjected to two surgical protocols: (1) lymphadenectomy plus irradiation; and (2) sham surgery and no irradiation. Head and neck expansion was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A host of other tape measurement protocols have been described, ranging from 3 to 11 tape measurements in total, each with very limited support in the literature 23–25,47,55–57 . As alternatives to tape measurements, digital photography with clinician analysis of serial photographs has been utilized in two studies 31,32 ; and electronic calipers were used in a recent animal model of HNL, though their use in the clinical setting has as yet not been published 12 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A host of other tape measurement protocols have been described, ranging from 3 to 11 tape measurements in total, each with very limited support in the literature 23–25,47,55–57 . As alternatives to tape measurements, digital photography with clinician analysis of serial photographs has been utilized in two studies 31,32 ; and electronic calipers were used in a recent animal model of HNL, though their use in the clinical setting has as yet not been published 12 …”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25]47,[55][56][57] As alternatives to tape measurements, digital photography with clinician analysis of serial photographs has been utilized in two studies 31,32 ; and electronic calipers were used in a recent animal model of HNL, though their use in the clinical setting has as yet not been published. 12 For the purposes of diagnosis and classification, the key advantage of measurement protocols is their objectivity relative to rating scales, while still being easily performed at the bedside by a range of trained providers. This objectivity is significant, given that a meta-analysis of lymphedema of all types in 2010 reported that studies using objective methods of assessment were twice as likely to diagnose patients with lymphedema relative to studies using subjective methods.…”
Section: Clinician-reported Assessment Methods: Measurement Protocolsmentioning
confidence: 99%
See 3 more Smart Citations